Trade in Services Related to Climate Change An Exploratory Analysis - Steenblik, Ronald (OECD Publishing, 2011)
The deployment of technologies for the mitigation of greenhouse-gases (GHGs) is dependent on a wide range of services, including those that are imported. Business services, telecommunications services, and construction and related engineering services figure prominently. This paper aims to develop a better understanding of the specific roles that these services play in helping to mitigate GHG emissions, and to identify the major suppliers and consumers. It presents examples and mini-case studies that explore how particular services complement the deployment of GHG mitigating technologies. With respect to the four modes of services trade, instances of mode 1 (cross-border trade) trade taking place over the Internet appear to be more commonplace, often complementing movement of personnel. Examples of mode 2 trade (consumption abroad) typically involve training of a client's personnel. Mode 3 trade (commercial presence) is critical for the provision of services that entail construction and operation of production facilities. The temporary movement of natural persons (mode 4) is also common, especially where expert judgement or supervision is required for a short period of time
Keywords: Environment; Trade